Solve for X. e^2x - 3e^x + 2=0     

Expert Answers

An illustration of the letter 'A' in a speech bubbles

e^2x-3e^x +2 =0

Let us assume that e^x =y.

Now substitute:

==> y^2 -3y +2 =0

Factorize:\

(y-2)(y-1)=0

y1= 2 ==> y1=e^x1= 2 ==> x1=ln2

y2=1 ==> y2=e^x2= 1 ==> x2=0

The solution for the equation is :

x= {0, ln2}

Approved by eNotes Editorial Team
Soaring plane image

We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

  • 30,000+ book summaries
  • 20% study tools discount
  • Ad-free content
  • PDF downloads
  • 300,000+ answers
  • 5-star customer support
Start your 48-Hour Free Trial